Conceptualizing How Caregiving Relationships Connect to Quality of Family Caregiving within the Stress Process Model. Issue 6 (18th August 2022) - Meyer, Kylie N.; Glassner, Ashlie; Lee, Kyungmi; Pickering, Carolyn E. Z.; White, Carole L.
ABSTRACT: Family caregivers provide the majority of care for older and disabled family members living with an illness or disability. Although most caregivers want to provide high-quality care, many report providing care that is potentially harmful. We apply the Stress Process Model to review the preponderance of literature implicating quality of the relationship between caregivers and care recipients as a factor contributing to quality of family caregiving. In drawing together literature on caregiving relationships and caregiving quality, this commentary identifies potentially modifiable intervention targets to develop programs to support high-quality caregiving to older adults living with a chronic illness or disability.